اولی الامر کے بنیادی اوصاف: اسوۂ رسول ﷺ و خلفائے راشدین کی روشنی میں ایک مطالعہ: Basic Characteristics of the Rulers: A Study in the Light of the Practices of the Prophet and the Righteous Caliphs (Al-Qamar, 2019)
The acts of a person become precious when they are in accordance with the shariah method and prophetic tradition. The teachings of Prophet (P.B.U.H) are a source of guidance for people related to every department of life. In Islamic shariah, there is a perfect and defined method for every worship. Similarly, for governors, leaders and scholars also, there are some finest attributes that will adorn their personalities so that they can become a role model/ ideal for their subordinates. Being a ruler and ruling the state, being a governor and taking charge of the state, as a scholar being a guide is also a kind of worship and this worship can only be understood in the light of the teachings of prophet (P.B.U.H) and the guided caliphs. In this article, the qualities of the above-mentioned personalities will be discussed adopting which would enhance the character of any official personnel.
Keywords: Rulers; attributes; Prophet; Saḥaba